Tactic of Involving a Specialist in Interrogation - Makarova, Olena (Archives of Criminology and Forensic Sciences, 2024)
The research paper considers the methods of interacting with specialists and analyzes a situation when involvement of specialists in interrogation is required or recommended. The article contains practical advice for law enforcement agencies and investigators on planning and conducting investigative (search) actions in criminal proceedings. The author has analyzed tactical techniques that investigators can apply to utilize specialists and their expertise during interrogations and other actions. Emphasis is placed on how the determining role of specialists can affect decisions and strategies in trial. The author studies potential risks and benefits associated with the involvement of specialists and provides practical guidelines for optimizing this process. The author emphasizes the importance of careful planning and coordination of efforts of all participants in a criminal proceeding in order to obtain the best results in specific expertise use